Camera trapping as a method for monitoring rhino populations within the Waterberg Plateau Park, Namibia - Stein, A.; Erckie, B.; Fuller, T.; Marker, L. (Pachyderm, 2010)
For species with unique markings, camera trapping has been used as a non-invasive method for generating population estimates and monitoring the fate of particular individuals. Rhinos—both black (Diceros bicornis) and white (Ceratotherium simum)—have unique horn sizes, shapes and scarring, making camera trapping a monitoring technique that could be useful. Over a 7-week period during 2006 in the Waterberg Plateau Park (WPP) in Namibia, we obtained 125 photos of rhinos from 11 camera stations during 545 camera nights, about half of which were useful in identifying 18 individual black rhinos and 13 white rhinos. Additional coverage of the Park could lead to more complete counts that would complement ongoing monitoring efforts. Key words: camera trapping, monitoring, black rhino, white rhino, Namibia Pour des espèces ayant des marques uniques, le piégeage photographique a été utilisé comme une méthode non envahissante pour produire des évaluations des populations et surveiller la situation des individus particuliers. Les rhinocéros noirs (Diceros bicornis) et blancs (Ceratotherium simum) ont la taille des cornes, des formes et des marques uniques, rendant le piégeage photographique une technique de surveillance qui pourrait être utile. En 2006, sur une période de sept semaines nous avons obtenu 125 photos de rhinocéros de 11 stations photographiques pendant 545 nuits de photographie au Parc du plateau de Waterberg en Namibie, dont environ la moitié servait à identifier 18 différents rhinocéros noirs et 13 rhinocéros blancs. Une couverture supplémentaire du parc pourrait mener à des comptages plus complets qui compléteraient les efforts de surveillance en cours.